Histone deacetylase HDAC1 expression correlates with the progression and prognosis of lung cancer: A meta-analysis. Issue 31 (August 2017) - Cao, Lin-Lin; Song, Xiaoxu; Pei, Lin; Liu, Lianhua; Wang, Hui; Jia, Mei
Abstract: Background: Histone deacetylase 1 (HDAC1) is an important epigenetic factor, and is thought to be associated with the progression and prognosis of some types of cancer. HDAC1 has been reported to be overexpressed in lung cancer, but the correlation between HDAC1 overexpression and the clinical features or prognosis of lung cancer is controversial. In this study, we investigated the potential association between HDAC1 and lung cancer. Materials and Methods: Embase, Web of Science, PubMed, and other sources were searched for relevant studies. Pooled odds ratios (ORs) or hazard ratios (HRs) with 95% confidence interval (CI) were calculated to evaluate the association of HDAC1 with lung cancer risk. Results: Eight eligible studies were included in the final meta-analysis. We found that HDAC1 mRNA or protein expression was closely associated with the differentiation grade of lung cancer (OR = 2.36, 95% CI = 1.14–4.87, P = .02). In addition, the protein expression level of HDAC1 in squamous cell carcinoma was higher than that in adenocarcinoma (OR = 1.81, 95% CI = 1.13–2.90, P = .01). Finally, HDAC1 mRNA or protein expression was negatively correlated with the overall survival rate of patients with lung cancer (HR = 2.40, 95% CI = 1.48–3.88, P = .0004). Conclusion: In this meta-analysis, our results suggest that HDAC1 may serve as a good diagnostic and prognostic marker for lung cancer. Abstract : Supplemental Digital Content is available in the text